Diagnosis of tuberculous cervicitis by Papanicolaou-stained smear - Jaiprakash, Padmapriya (Ann Saudi Med, 2013)
Tuberculosis (TB) is a common infection in the developing countries. It can involve most organs. Genital TB is usually secondary to pulmonary or extragenital TB. Tuberculosis most commonly involves the upper genital tract. Involvement of the cervix is rare. In countries like India, where carcinoma of cervix is very common, cervical TB may easily be mistaken clinically for malignancy. We report a case of tuberculosis cervicits (secondary to pulmonary tuberculosis) in a 54-year-old postmenauposal woman, who presented with a complaint of discharge per vaginum for a short duration. Per speculum examination showed an ulcerated lesion over anterior lip of cervix, clinically suggestive of malignancy. However, a Papanicolaou-smear showed features suggestive of tuberculosis which was confirmed by biopsy, resulting in early diagnosis and treatment of the patient. Hence, in a patient with a suspicious cervical lesion and a prior history of tuberculosis, a diagnosis of cervical tuberculoiss must be considered.